Fungal communities in the garden chamber soils of leaf-cutting ants - Rodrigues, Andre; Passarini, Michel R. Z.; Ferro, Milene; Nagamoto, Nilson S.; Forti, Luiz C.; Bacci, Maurício [UNESP]; Sette, Lara D.; Pagnocca, Fernando C. (Wiley, 2013)
Leaf-cutting ants modify the properties of the soil adjacent to their nests. Here, we examined whether such an ant-altered environment impacts the belowground fungal communities. Fungal diversity and community structure of soil from the fungus garden chambers of Atta sexdens rubropilosa and Atta bisphaerica, two widespread leaf-cutting ants in Brazil, were determined and compared with non-nest soils. Culture-dependent methods revealed similar species richness but different community compositions between both types of soils. Penicillium janthinellum and Trichoderma spirale were the prevalent isolates in fungus chamber soils and non-nest soils, respectively. In contrast to cultivation methods, analyses of clone libraries based on the internal transcribed spacer (ITS) region indicated that richness of operational taxonomic units significantly differed between soils of the fungus chamber and non-nest soils. FastUnifrac analyses based on ITS sequences further revealed a clear distinction in the community structure between both types of soils. Plectania milleri and an uncultured Clavariaceae fungus were prevalent in fungus chamber soils and non-nest soils, respectively. FastUnifrac analyses also revealed that fungal community structures of soil from the garden chambers markedly differed among ant species. Our findings suggest that leaf-cutting ants affect fungal communities in the soil from the fungus chamber in comparison to non-nest soils. © 2013 WILEY-VCH Verlag GmbH & Co.
Keywords: Filamentous fungi; ITS sequencing; Tribe Attini; Yeasts